2018
DOI: 10.20546/ijcmas.2018.711.268
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Architecture of Some Economic Traits in Okra (Abelmoschus esculentus (L.) Moench) through Generation Mean Analysis

Abstract: The nature and magnitude of gene action was analysed using six generations viz., P 1 , P 2 , F 1 , F 2 , BC 1 and BC 2 for yield and yield contributing characters in four inter varietal crosses of okra. The scaling and joint scaling tests indicated the presence of epistatic gene effect for all the characters in four crosses. Duplicate epistasis was predominant in most of the yield and yield attributing characters in all the four crosses except number of fruits per plant, which showed complimentary epistasis. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 6 publications
3
3
0
Order By: Relevance
“…Complementary epistasis for plant height was also reported by Deshmukh et al (2021) in all six crosses they studied. Similar findings were reported by Srikanth et al (2018).…”
Section: Number Of Fruiting Nodessupporting
confidence: 92%
See 4 more Smart Citations
“…Complementary epistasis for plant height was also reported by Deshmukh et al (2021) in all six crosses they studied. Similar findings were reported by Srikanth et al (2018).…”
Section: Number Of Fruiting Nodessupporting
confidence: 92%
“…Das et al (2013) and Soher et al (2013) also observed non-additive gene action for this trait. Similar epistatic interactions were also reported by Srikanth et al (2018) and Arora et al (2007). Among epistatic interactions additive x dominance (j) and dominance x dominance (l) interactions were significant.…”
Section: Number Of Fruiting Nodessupporting
confidence: 90%
See 3 more Smart Citations